Factors inﬂuencing the level of ethics and integrity in Malaysian public sector - Asmawati, Sajari; Hasnah, Hj Haron; Ganesan, Yuvaraj; Khalid, Azam Abdelhakeem (Emerald Publishing, 2023)
The aim of this study is to look into the factors that influence the level of ethics and integrity in Malaysian public sector. Design/methodology/approach: This study uses a quantitative approach by delivering 128 questionnaires to Federal Chief Integrity Officers (CIOs), of which 83 were received and usable. The data were analysed using multiple regression analysis and descriptive statistics. Findings: The quality of CIO in terms of competency, work performance and ethical climate has significant impact on the level of ethics and integrity. According to the study, having certified CIOs who can effectively perform their function and promote and nurture a transparent ethical climate are critical for the Malaysian Federal government to maintain a high level of ethics. Employees who have a high level of ethics are more likely to stay with the organization. Practical implications: In addition, this study will assist policymakers in taking the required actions to strengthen public sector integrity practices for the establishment of a more dependable and efficient government in Malaysia. Originality/value: This study addresses a gap in the Malaysian public sector’s level of ethics and integrity.